Global Stability Analysis of a TCP/AQM protocol for arbitrary networks with delay - Papachristodoulou, A; ieee (2004)
We investigate global stability of Fast AQM Scalable TCP (FAST), a network congestion control scheme for the Internet modelled by a nonlinear delay differential equation with heterogeneous delays. The stability conditions resemble the ones from the linearization, are delay-dependent and scalable for arbitrary network sizes; the special structure of the system and the choice of TCP/AQM dynamics allow the construction of appropriate Lyapunov-Krasovskii functionals in a scalable way.